THE RELATIONSHIP BETWEEN LEARNING STYLES AND USING OF POWERPOINT PRESENTATION TOWARD STUDENTS’ ENGLISH ACHIEVEMENT - Firdaus Ditya Pamungkas; Rizqi Akbarani (Institut Agama Islam Negeri (IAIN) Ponorogo, 2022)
Every student has different learning style where learning style is one of individual factor in second language acquisition. Using media also affect the students’ achievement, where using media can help students to learn and understand about material in teaching learning process. Understanding the learning style and using media can affect the students’ English achievement where achievement is as result of measurement and evaluation in learning for a period of time. It cannot be achieved if the students do not learn before. This research used power point presentation as media to help the teacher and student in learning process. This research aimed to describe about the relationship between students’ learning style and using of power point presentation toward their achievement in English learning. The method which was used in this research was survey method through correlational research. The population of the research was the second semester of students of majoring in Al Quran and Tafsir Ushuluddin, Adab and Dakwah Faculty IAIN Ponorogo in the 2021/2022 academic year. However, only class of IAT. B was chosen as the sample by using purposive sampling. Furthermore there were three variables in this research. The first one was students’ learning style (variable Xx), the second one was students’ perception in using of power point presentation (variable Xy), and the last was students’ achievement in English learning (variable Y). The students’ learning style score and students’ perception about using of power point presentation were taken from the questionnaire whereas the student’ achievement in English learning was taken from documentation. In analyzing the data and testing the hypothesis, the writer used SPSS 16 to found the correlation statistic where the results of pearson correlation is r = 0.171 with sig. (2-tailed) = 0.366 where 0.366 > 0.05. It means that null hypothesis (H) is accepted and the alternative hypothesis (Ha) is rejected. From the research finding, it can be concluded that there was no significant relationship between students’ learning style and using of power point presentation toward their achievement in English learning. It means that students’ learning style and using of media power point presentation is not a dominant factor that affects the students’ achievement. In this case, other factors such as motivation, aptitude, cognitive ability, and any other factors are maybe more dominant in affecting students’ English achievement than students’ learning style. Keywords: Sensory learning styles, using of power point presentation, students’ English achievement